Argumentasi Teologis dalam Kisah Rut: Implementasi Hukum Levirat dan Tanggung Jawab Sosial - Sinaga, Zuvico; Priyono, Joko (Sekolah Tinggi Teologi Injili Indonesia Samarinda, 2024)
Talking about redemption, the Old Testament directs us to a book that tells about redemption, namely the book of Ruth. This book talks about levirate marriage. According to Torah law, if a man dies without having children, his brother is obliged to take his wife in a